Sarcopenia and length of hospital stay - Sousa, A.S. (2015)
BACKGROUND/OBJECTIVES: We aimed to quantify the association of sarcopenia with length of hospital stay (LOS) and to identify factors associated with sarcopenia among hospitalized patients. SUBJECTS/METHODS: A total of 655 patients composed the study sample. A longitudinal study was conducted in a University Hospital. Sarcopenia was defined, according to European Consensus criteria, as low muscle mass (bioelectrical impedance analysis) and low muscle function (handgrip strength). Logistic regression, Kaplan-Meier and Cox adjusted proportional hazards methods were used. LOS was determined from the date of hospital admission and discharge home (event of interest). RESULTS: Participants were aged 18 to 90 years (24.3% sarcopenic). Factors associated with sarcopenia were male gender, age ⩾65 years, moderate or severe dependence, undernutrition and being admitted to a medical ward. Sarcopenic patients presented a lower probability of being discharged home (hazard ratio (HR), 95% confidence interval (CI) = 0.71, 0.58-0.86). However, after stratifying for age groups, this effect was visible only in patients aged o65 years (HR, 95% CI = 0.66, 0.51-0.86). Moreover, sarcopenic overweight or obese patients presented a higher probability of being discharged home (HR, 95% CI = 0.78, 0.61-0.99) than nonoverweight sarcopenic patients (HR, 95% CI = 0.63, 0.48-0.83). CONCLUSIONS: Being male, age ⩾65 years, presenting dependence, being undernourished and admitted to a medical ward were factors associated with sarcopenia among hospitalized adult patients. Sarcopenia is independently associated with longer LOS, although this association is stronger for patients aged o65 years. Moreover, sarcopenic overweight was associated with a higher probability of discharge home than nonoverweight sarcopenia.